Undiscovered voices: Motivation and demotivation factors in learning English among Indonesian orphan students - Zidni Ma’ruf; Bambang Widi Pratolo; Okta Widia Sari; Arlischa Ardinengtyas (Institute of Advanced Engineering and Science, 2022)
This qualitative descriptive research aimed to investigate factors of motivation and demotivation in learning English among Indonesian orphan students. There were eight participants who live and study in an Indonesian orphanage. They were randomly chosen in this research. The data were mainly collected through individual semi-structured interviews and focus group discussion (FGD) sections. All interviews and FGD sections data were recorded, transcribed, analyzed, and divided into several themes and subthemes. Further, member checking was done to develop the trustworthiness of the research. The research revealed that internal and external factors were positively related to motivation and demotivation in learning English among Indonesian orphan students. Further, suggestions and policy recommendations were all offered to related parties to support and give equal educational facilities to all students since they have the same right for education.